Effects of clove oil on behavioral reactivity and motivation in Nile tilapia - da Silva, Dneson Ricardo [UNESP]; Arvigo, Alexandre Luiz [UNESP]; Giaquinto, Percília Cardoso [UNESP]; Delicio, Helton Carlos [UNESP]; Barcellos, Leonardo José Gil; Barreto, Rodrigo Egydio [UNESP] (Elsevier, 2021)
Essential oils have been used as potential substitutes for synthetic anesthetics in aquaculture. In this context, the oil extracted from parts of the clove plant (Eugenia caryophyllata) has been used as anesthetic. This oil has been considered effective, since induces anesthesia quickly, reflex recovery is brief and has low mortality rate. However, it is unknown whether there are changes in stimuli reactivity and behavioral motivational in fish after anesthesia recovery. As the effects of anesthetics are on the central nervous system, it is plausible to assume such possibilities. Here we tested this hypothesis using Nile tilapia, a relevant species for aquaculture. Operationally, we measured elements of feeding and aggressive behaviors to infer effects on reactivity to stimuli and motivation. For this, using the bath exposure technique, we submitted the fish to 3 different conditions: 1) negative control (without anesthetic) and two alcoholic solutions of clove oil diluted in water 2) 50 mg/l and 3) 100 mg/l. Tilapia were anesthetized by bathe exposure into buckets until reach the classic stage II of anesthesia. After, they were introduced into test aquaria (1 fish per aquarium) for future observations. Control fish (0 mg/L) were exposed to the same procedures and remained into the buckets until the longest period for one of the fish in the batch to reach stage II of anesthesia. Tilapia were kept in the aquaria for 4 consecutive days and, while the feeding behavior was evaluated daily, the aggressive behavior was evaluated on the second and fourth days. Here, we provide evidences that clove oil did not affect reactivity to stimuli and motivation regarding these evaluated behaviors. Thus, we reinforce the safe use of clove oil in aquaculture practices that require anesthesia in fish.
Keywords: Aggression; Anesthesia; Clove oil; Essential oil; Feeding behavior